2008
DOI: 10.1111/j.1365-2893.2008.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow‐derived mesenchymal stem cells are capable of mediating hepatitis B virus infection in injured tissues

Abstract: These results indicate that MSCs could serve as an additional extrahepatic virus reservoir, which may play a role at least in part in mediating HBV trans-infection into the injured tissues through the process of MSCs recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
2
8
0
1
Order By: Relevance
“…Alternatively, BM-MSCs may secrete cytokines, including fibroblast growth factor (42,43), epidermal growth factor (EGF) (44), and hepatocyte growth factor (HGF) (43,45,46) to inhibit HBV replication (47). In addition, intracellular HBV cccDNA in BM-MSCs co-cultured with HepG2.2.15 cells was not detected, which supports the conclusion that HBV is unable to replicate in BM-MSCs (48,49). …”
Section: Discussionsupporting
confidence: 66%
“…Alternatively, BM-MSCs may secrete cytokines, including fibroblast growth factor (42,43), epidermal growth factor (EGF) (44), and hepatocyte growth factor (HGF) (43,45,46) to inhibit HBV replication (47). In addition, intracellular HBV cccDNA in BM-MSCs co-cultured with HepG2.2.15 cells was not detected, which supports the conclusion that HBV is unable to replicate in BM-MSCs (48,49). …”
Section: Discussionsupporting
confidence: 66%
“…We show that nonliver‐derived mesenchymal stem cells (UCMSCs) are turned permissive to the entire HBV life cycle upon in vitro hepatogenic differentiation. None of the few studies conducted on in vitro infection of other MSCs evaluated binding and uptake kinetics 28, 29. We set up infection conditions in order to analyze the different steps of the viral cycle and demonstrated that, although replication efficiency downstream of viral entry was quite low, HBV uptake was fully supported by D‐UCMSCs and comparable to PHHs.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, BM-MSCs obtained from healthy donors fully supported HBV infection, replication, expression, and secretion, which could make the MSCs a reservoir of virus [ 42 ]. Furthermore, it has been reported that MSCs can serve as an extrahepatic virus reservoir by harboring and transporting HBV to the injured tissues after transplantation of HBV-exposed MSCs into myocardial infarction (MI) mouse model [ 47 ]. Although autologous BM-MSCs were resistant to HBV infection and were proven to be safe for transplantation, obtaining autologous BMSCs from chronic hepatitis B patients is too invasive and may cause distress to patients.…”
Section: Safety In Using Mscs As Cellular Therapy In Virus-relatedmentioning
confidence: 99%